2016
DOI: 10.1016/j.vaccine.2016.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of oral cholera vaccine and reasons for full, partial and non-acceptance during a humanitarian crisis in South Sudan

Abstract: (300 words max):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 9 publications
5
30
0
1
Order By: Relevance
“…53 The other two vaccination studies focused on specific diseases and aims: yellow fever vaccination administration and effectiveness 44 and IDP perception of cholera vaccination. 54 Both studies reported exceeding the 90% WHO vaccination coverage standard requirement; and the high coverage level was linked to the IDPs' high of level awareness about the disease severity. 54 These coverage assessments were however based on self-reports since most IDPs had no vaccination cards to present as evidence.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…53 The other two vaccination studies focused on specific diseases and aims: yellow fever vaccination administration and effectiveness 44 and IDP perception of cholera vaccination. 54 Both studies reported exceeding the 90% WHO vaccination coverage standard requirement; and the high coverage level was linked to the IDPs' high of level awareness about the disease severity. 54 These coverage assessments were however based on self-reports since most IDPs had no vaccination cards to present as evidence.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
“…54 Both studies reported exceeding the 90% WHO vaccination coverage standard requirement; and the high coverage level was linked to the IDPs' high of level awareness about the disease severity. 54 These coverage assessments were however based on self-reports since most IDPs had no vaccination cards to present as evidence. 44 There were observed slight reductions in the number of IDPs vaccinated compared to the total numbers initially informed of the vaccination schedule.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
See 3 more Smart Citations